Sex Differences in Perceptions of Infidelity: Men Often Assume the Worst - Aaron T. Goetz; Kayla Causey (Evolutionary Psychology, 2009)
Given that the costs of underperceiving (i.e., failing to detect) a partner's sexual infidelity would have been greater for men than for women, we hypothesized that men may possess evolved psychological mechanisms designed to overperceive the likelihood of their partner's sexual infidelity. We found support for this hypothesis using two different response formats, a Likert-type scale (Study 1) and a visual analog scale (Study 2). In both studies, men were more likely than women to judge that their partners would commit sexual infidelity in the future. Discussion addresses additional design features of the infidelity detection system.